A dual flip angle 3D bSSFP magnetization transfer‐like method to differentiate between recent and old myocardial infarction. Issue 3 (20th July 2017) - Germain, Philippe; El Ghannudi, Soraya; Labani, Aissam; Jeung, Mi Y.; Gangi, Afshin; Ohlmann, Patrick; Roy, Catherine
Abstract : Background: Magnetic resonance imaging (MRI) tissue signal is modulated by magnetization transfer (MT) phenomena, intrinsically induced by balanced steady‐state free precession (bSSFP) imaging. Purpose: To investigate the possible value of such a MT‐like bSSFP approach in two clinical settings involving focal myocardial lesions highligthed by late gadolinium enhancement (LGE+): edema induced by recent myocardial infarction (MI) and fibrotic scar related to chronic infarction. Materials and Methods: Population: 48 LGE + patients were studied: 26 with recent MI, 22 with chronic MI. 20 LGE‐normal subjects were considered the control group. Field strength/sequence: Navigator‐based short axis 3D‐bSSFP sequences with 20° and 90° excitation flip angles were acquired (1.5T). Assessment: Pixel‐wise normalized MT Ratio (nMTR) parametric images were calculated according to: nMTR = 100*(S20 ‐S90 *k)/S20, with S20 and S90 signal intensity in 20° and 90° flip angle images and k = Blood20 /Blood90 as a normalization ratio. Statistical tests: analysis of variance (ANOVA), receiver operating characteristic (ROC) analysis. Results: Overall normal myocardial nMTR was 50.2 ± 3.6%. In recent MI, nMTR values were significantly reduced in LGE + regions (–22.3 ± 9.9%, P < 0.0001). In cases of chronic infarct, nMTR was significantly increased in LGE + regions (14.2 ± 11.4%, P < 0.0001). Comparison between observed results and theoretical values obtained with the Freeman‐Hill formula showed that most variations observed in MI are related to MT effects instead of relaxation effects. Conclusion: In contrast to LGE imaging, which may show a similar hyperenhancement in recent and old infarctions, nMTR imaging demonstrates an opposite pattern: decreased values for recent infarction and increased values for old infarction, thus allowing to discriminate between these two clinical conditions without gadolinium injection. Level of Evidence : 3 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2018;47:798–808.